Effect of Lactic Acid Etching on Bonding Effectiveness of Orthodontic Bracket after Water Storage. (17th March 2014) - Alsulaimani, Fahad F.
Abstract : Objective . To determine the effect of lactic acid at various concentrations on the shear bond strength of orthodontic brackets bonded with the resin adhesive system before and after water storage. Materials and Methods . Hundred extracted human premolars were divided into 5 treatment groups and etched for 30 seconds with one of the following agents: lactic acid solution with (A) 10%, (B) 20%, (C) 30%, and (D) 50%; group E, 37% phosphoric acid (control). Metal brackets were bonded using a Transbond XT. Bonding effectiveness was assessed by shear bond strength after 24 hours and 6 months of water storage at 37°C. The data were analyzed with 2-way analysis of variance and Tukey's Honestly Significant Difference (HSD) test (α = . 001 ). Results . Lactic acid concentration and water storage resulted in significant differences for brackets bond strength (P < . 001 ). 20% lactic acid had significantly higher mean bond strength values (SD) for all conditions: 24 hours [12.2 (.7) MPa] and 6 months [10.1 (.6) MPa] of water storage. 37% phosphoric acid had intermediate bond strength values for all conditions: 24 hours [8.2 (.6) MPa] and 6 months [6.2 (.6) MPa] of water storage. Also, there were differences in bond strength between storage time, with a reduction in values from 24 hours and 6 months for all experimental groups (P < . 001 ). Conclusion . Lactic acid could be used in place of phosphoric acid as an enamel etchant for bonding of orthodontic brackets.